A long-life lead-carbon battery positive electrode formula and production process
By adopting specific positive electrode formulas and production processes of lead-carbon batteries, the problem of poor strength of positive electrode active substances in existing batteries is solved, and the long life and efficient performance of the battery are achieved.
Patent Information
- Application Number
- CN202411841003.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-01
AI Technical Summary
The strength of the positive electrode active substance of existing lead-acid batteries is poor, resulting in a shortening of the battery life.
A long-life lead-carbon battery positive electrode formula is adopted, including lead powder, dilute sulfuric acid, pure water, stannous sulfate, red dan, antimony trioxide, cobalt sulfate, sodium phosphate, high-purity graphite, vapor-phase silica and high-strength staple fibers. The electrode plate is formed through dry stirring, wet stirring, acid stirring and curing processes, and finally the chemical formation process is carried out.
It improves the energy density and cycle life of the battery, reduces the internal resistance of the plate, enhances the bonding strength and plate strength between active substances, and extends the service life of the battery.
Smart Images

Figure CN119742330A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lead-acid battery production, and in particular to a long-life lead-carbon battery positive electrode formula and a production process. Background Art
[0002] During the charge and discharge process of lead-acid batteries, the positive electrode is converted from lead sulfate to lead dioxide during charging, resulting in a volume contraction, and when discharged, it is converted from lead dioxide to lead sulfate, resulting in a volume expansion. The density of lead dioxide is 9.36 g / cm 3 , the density of lead sulfate is 6.23g / cm 3 The battery will inevitably shrink and expand during the charging and discharging process. The existing positive active material has poor strength, which leads to poor strength of the corrosion layer between the positive active material and the grid, resulting in a large internal resistance at the junction of the active material and the ribs, which will aggravate the softening and shedding of the active material, thereby shortening the cycle life of the battery. Summary of the invention
[0003] The purpose of the present invention is to provide a long-life lead-carbon battery positive electrode formula and production process to solve the problem that the existing battery positive electrode active material has poor strength, resulting in a shortened battery life.
[0004] In order to solve the above problems, the technical solutions provided are as follows:
[0005] A long-life lead-carbon battery positive electrode formula, which mainly includes the following raw materials by mass percentage:
[0006] Lead powder 80%~85%, dilute sulfuric acid 4%~8%, pure water 5%~10%, stannous sulfate 0.05%~0.08%, red lead 1.5%~3%, antimony trioxide 0.05%~0.08%, cobalt sulfate 0.1%~0.5%, sodium phosphate 0.1%~0.5%, high-purity graphite 2.5%~3.5%, fumed silica 0.3%~0.5%, high-strength short fiber 0.04%~0.06%.
[0007] The beneficial effects of the above formula are: cobalt sulfate and sodium phosphate increase the oxidizability, thereby improving the energy density and cycle life of the battery; sodium phosphate increases the oxidizability, improves the corrosion bonding between the active substance and the grid, thereby extending the cycle life of the battery; high-purity graphite optimizes the positive plate formula, increases conductivity, reduces the internal resistance of the plate, and reduces irreversible sulfation; fumed silica enhances the bonding strength between active substances, while increasing the internal porosity and acid content of the plate, thereby improving high-current discharge performance; high-strength short fibers enhance the bonding ability between active substances and improve the strength of the plate.
[0008] A long-life lead-carbon battery positive electrode production process comprises the following steps:
[0009] S1: Material collection: Weigh 80% to 85% of lead powder and additives, the additives include 0.05% to 0.08% of stannous sulfate, 1.5% to 3% of red lead, 0.05% to 0.08% of antimony trioxide, 0.1% to 0.5% of cobalt sulfate, 0.1% to 0.5% of sodium phosphate, 2.5% to 3.5% of high-purity graphite, 0.3% to 0.5% of fumed silica, and 0.04% to 0.06% of high-strength short fibers.
[0010] S2: Dry mixing: Add the raw materials of step S1 into a vacuum paste machine and dry mix for 180 seconds;
[0011] S3: Wet mixing: Add pure water to the vacuum paste machine and wet mix for 240 seconds;
[0012] S4: Acid stirring: Add 1.400g / cm 3 4% to 8% dilute sulfuric acid is stirred for 10 to 20 minutes to obtain lead paste, 1.400g / cm 3 Dilute sulfuric acid is added in several portions;
[0013] S5: Plate production: Apply lead paste on the mesh belt to form the plate.
[0014] S6: Curing: Remove the plate and place it on the curing rack, then push the curing rack into the curing room for curing. The curing includes a high humidity stage, an oxidation stage and a drying stage. The high humidity stage lasts for 24 to 30 hours, the oxidation stage lasts for 15 to 20 hours, and the drying stage lasts for 15 hours.
[0015] S7: Formation: After the cured plates are assembled into semi-finished batteries, they are formed by a process of eight charges and seven discharges.
[0016] The beneficial effects of the above technical solution are:
[0017] 1. Reduce the amount of gas precipitation from the positive plate, reduce the impact on the grid and active materials, extend the corrosion resistance of the grid, use high-purity graphite to increase conductivity and reduce the internal resistance of the plate, and reduce irreversible sulfation phenomenon;
[0018] 2. Use fumed silica, cobalt sulfate, sodium phosphate and high-strength short fibers with high toughness and dispersibility to increase the strength between active substances, delay the softening and shedding of active substances, improve the plate porosity and plate strength, reduce the diffusion resistance of divalent lead ions into the plate, increase the utilization rate of active substances, and increase the high-current discharge performance of the battery;
[0019] 3. The curing process ensures the corrosion bonding layer between the positive electrode active material and the grid, reduces the internal resistance, improves the plate strength, and increases the battery life;
[0020] 4. The formation process fully guarantees the conversion of active substances during formation and extends the battery's cycle life.
[0021] Preferred solution 1: As a further optimization of the basic solution, the lead powder in step S2 is divided into two portions and added to the vacuum paste machine twice. The first portion is first added to the vacuum paste machine, then the additive is added and stirred, and the second portion is added to the vacuum paste machine.
[0022] Preferred solution 2: As a further optimization of preferred solution 1, the time for adding pure water in step S3 is controlled within 80 seconds.
[0023] Preferred solution three: As a further optimization of preferred solution two, in step S4, dilute sulfuric acid is added in a total of 6 times, the first acid addition amount is 25% / vacuum degree 535mba / 160 seconds, the second acid addition amount is 30% / vacuum degree 530mba / 156 seconds, the third acid addition amount is 25% / vacuum degree 435mba / 156 seconds, the fourth acid addition amount is 10% / vacuum degree 425mba / 55 seconds, the fifth acid addition amount is 5% / vacuum degree 280mba / 28 seconds, and the sixth acid addition amount is 5% / vacuum degree 180mba / 22 seconds.
[0024] Preferred solution 4: As a further optimization of preferred solution 3, the paste temperature in step S4 is controlled within 45°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a process flow chart of an embodiment of the present invention;
[0026] Figure 2 It is a line graph of the durability test data of the battery according to the embodiment of the present invention and the existing battery. DETAILED DESCRIPTION
[0027] The following is further described in detail through specific implementation methods:
[0028] The embodiment is basically as shown in the attached Figure 1-2 As shown:
[0029] A long-life lead-carbon battery positive electrode formula, which mainly includes the following raw materials by mass percentage:
[0030] Lead powder 80%~85%, dilute sulfuric acid 4%~8%, pure water 5%~10%, stannous sulfate 0.05%~0.08%, red lead 1.5%~3%, antimony trioxide 0.05%~0.08%, cobalt sulfate 0.1%~0.5%, sodium phosphate 0.1%~0.5%, high-purity graphite 2.5%~3.5%, fumed silica 0.3%~0.5%, high-strength short fiber 0.04%~0.06%.
[0031] The specific implementation process is as follows:
[0032] Example 1
[0033] A long-life lead-carbon battery positive electrode production process, such as Figure 1 As shown, the following steps are included:
[0034] S1: Material collection: Weigh 80% of lead powder and additives, including 0.08% of stannous sulfate, 3% of red lead, 0.06% of antimony trioxide, 0.5% of cobalt sulfate, 0.5% of sodium phosphate, 2.5% of high-purity graphite, 0.3% of fumed silica and 0.06% of high-strength short fiber.
[0035] S2: dry stirring: the lead powder in step S1 is divided into two parts and added to the vacuum paste machine twice. The first part is added to the vacuum paste machine first, and then the additive is added for dry stirring. The second part is added to the vacuum paste machine for dry stirring. The whole stirring process is controlled within 180 seconds.
[0036] S3: Wet mixing: Add 5% pure water to the vacuum paste machine and wet mix for 240 seconds. The pure water addition time is controlled to be completed within 80 seconds;
[0037] S4: Acid stirring: Add 1.400g / cm 3 8% dilute sulfuric acid is stirred for 10 to 20 minutes to obtain lead paste. The paste temperature is controlled within 45°C, 1.400g / cm 3 Dilute sulfuric acid is added in six times, the first acid addition amount is 25% / vacuum degree 535mba / 160 seconds, the second acid addition amount is 30% / vacuum degree 530mba / 156 seconds, the third acid addition amount is 25% / vacuum degree 435mba / 156 seconds, the fourth acid addition amount is 10% / vacuum degree 425mba / 55 seconds, the fifth acid addition amount is 5% / vacuum degree 280mba / 28 seconds, and the sixth acid addition amount is 5% / vacuum degree 180mba / 22 seconds;
[0038] S5: Plate production: Apply lead paste on the mesh belt to form the plate.
[0039] S6: Curing: Remove the plate and place it on the curing rack, then push the curing rack into the curing room for curing. The curing includes a high humidity stage, an oxidation stage and a drying stage. The high humidity stage lasts for 24 to 30 hours, the oxidation stage lasts for 15 to 20 hours, and the drying stage lasts for 15 hours.
[0040] S7: Formation: After the cured plates are assembled into semi-finished batteries, they are formed by a process of eight charges and seven discharges, fully controlling the internal temperature of the battery during charging to be below 50°C, ensuring that the α-PbO2 content in the positive electrode is between 20% and 25%.
[0041] Example 2
[0042] A long-life lead-carbon battery positive electrode production process, such as Figure 1 As shown, the following steps are included:
[0043] S1: Material: Weigh 81% of lead powder and additives, including 0.05% of stannous sulfate, 1.5% of red lead, 0.08% of antimony trioxide, 0.1% of cobalt sulfate, 0.5% of sodium phosphate, 2.5% of high-purity graphite, 0.3% of fumed silica and 0.04% of high-strength short fiber.
[0044] S2: dry stirring: the lead powder in step S1 is divided into two parts and added to the vacuum paste machine twice. The first part is added to the vacuum paste machine first, and then the additive is added for dry stirring. The second part is added to the vacuum paste machine for dry stirring. The whole stirring process is controlled within 180 seconds.
[0045] S3: Wet mixing: Add 8% pure water to the vacuum paste machine and wet mix for 240 seconds. The pure water addition time is controlled to be completed within 80 seconds;
[0046] S4: Acid stirring: Add 1.400g / cm 3 6% dilute sulfuric acid is stirred for 10 to 20 minutes to obtain lead paste. The paste temperature is controlled within 45°C, 1.400g / cm 3 Dilute sulfuric acid is added in six times, the first acid addition amount is 25% / vacuum degree 535mba / 160 seconds, the second acid addition amount is 30% / vacuum degree 530mba / 156 seconds, the third acid addition amount is 25% / vacuum degree 435mba / 156 seconds, the fourth acid addition amount is 10% / vacuum degree 425mba / 55 seconds, the fifth acid addition amount is 5% / vacuum degree 280mba / 28 seconds, and the sixth acid addition amount is 5% / vacuum degree 180mba / 22 seconds;
[0047] S5: Plate production: Apply lead paste on the mesh belt to form the plate.
[0048] S6: Curing: Remove the plate and place it on the curing rack, then push the curing rack into the curing room for curing. The curing includes a high humidity stage, an oxidation stage and a drying stage. The high humidity stage lasts for 24 to 30 hours, the oxidation stage lasts for 15 to 20 hours, and the drying stage lasts for 15 hours.
[0049] S7: Formation: After the cured plates are assembled into semi-finished batteries, they are formed by a process of eight charges and seven discharges, fully controlling the internal temperature of the battery during charging to be below 50°C, ensuring that the α-PbO2 content in the positive electrode is between 20% and 25%.
[0050] Example 3
[0051] A long-life lead-carbon battery positive electrode production process, such as Figure 1 As shown, the following steps are included:
[0052] S1: Material: Weigh 85% of lead powder and additives, including 0.05% of stannous sulfate, 2% of red lead, 0.05% of antimony trioxide, 0.1% of cobalt sulfate, 0.1% of sodium phosphate, 2.5% of high-purity graphite, 0.3% of fumed silica and 0.04% of high-strength short fiber.
[0053] S2: dry stirring: the lead powder in step S1 is divided into two parts and added to the vacuum paste machine twice. The first part is added to the vacuum paste machine first, and then the additive is added for dry stirring. The second part is added to the vacuum paste machine for dry stirring. The whole stirring process is controlled within 180 seconds.
[0054] S3: Wet mixing: Add 6% pure water to the vacuum paste machine and wet mix for 240 seconds. The pure water addition time is controlled to be completed within 80 seconds;
[0055] S4: Acid stirring: Add 1.400g / cm 3 4% dilute sulfuric acid is stirred for 10 to 20 minutes to obtain lead paste. The paste temperature is controlled within 45°C, 1.400g / cm 3 Dilute sulfuric acid is added in six times, the first acid addition amount is 25% / vacuum degree 535mba / 160 seconds, the second acid addition amount is 30% / vacuum degree 530mba / 156 seconds, the third acid addition amount is 25% / vacuum degree 435mba / 156 seconds, the fourth acid addition amount is 10% / vacuum degree 425mba / 55 seconds, the fifth acid addition amount is 5% / vacuum degree 280mba / 28 seconds, and the sixth acid addition amount is 5% / vacuum degree 180mba / 22 seconds;
[0056] S5: Plate production: Apply lead paste on the mesh belt to form the plate.
[0057] S6: Curing: Remove the plate and place it on the curing rack, then push the curing rack into the curing room for curing. The curing includes a high humidity stage, an oxidation stage and a drying stage. The high humidity stage lasts for 24 to 30 hours, the oxidation stage lasts for 15 to 20 hours, and the drying stage lasts for 15 hours.
[0058] S7: Formation: After the cured plates are assembled into semi-finished batteries, they are formed by a process of eight charges and seven discharges, fully controlling the internal temperature of the battery during charging to be below 50°C, ensuring that the α-PbO2 content in the positive electrode is between 20% and 25%.
[0059] The obtained plates of Examples 1-3 were processed into 6-DMF-20 batteries. At the same time, similar products on the market were collected and tested according to industry standards for main indicators. The test comparison data are shown in Table 1 below. The line graph of the test comparison data is shown in Table 1 below. Figure 2 As shown:
[0060] Table 1: Durability test data of the embodiment of the present invention and the existing battery
[0061]
[0062]
[0063] According to the data in Table 1 and Figure 2 It can be seen from the line graph that the battery made by this scheme has a longer service life and better durability than the batteries on the market.
[0064] The above is only an embodiment of the present invention, and the common knowledge such as the known specific structure and characteristics in the scheme is not described in detail here. It should be pointed out that for those skilled in the art, several deformations and improvements can be made without departing from the structure of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A long-life lead-carbon battery positive electrode formula, characterized in that: According to the percentage by mass, it mainly includes the following raw materials: Lead powder 80%~85%, dilute sulfuric acid 4%~8%, pure water 5%~10%, stannous sulfate 0.05%~0.08%, red lead 1.5%~3%, antimony trioxide 0.05%~0.08%, cobalt sulfate 0.1%~0.5%, sodium phosphate 0.1%~0.5%, high-purity graphite 2.5%~3.5%, fumed silica 0.3%~0.5%, high-strength short fiber 0.04%~0.06%.
2. A process for producing a positive electrode for a long-life lead-carbon battery according to the formula of claim 1, characterized in that: The following steps are involved: S1: Material collection: Weigh 80% to 85% of lead powder and additives, the additives include 0.05% to 0.08% of stannous sulfate, 1.5% to 3% of red lead, 0.05% to 0.08% of antimony trioxide, 0.1% to 0.5% of cobalt sulfate, 0.1% to 0.5% of sodium phosphate, 2.5% to 3.5% of high-purity graphite, 0.3% to 0.5% of fumed silica and 0.04% to 0.06% of high-strength short fibers. S2: Dry mixing: Add the raw materials of step S1 into a vacuum paste machine and dry mix for 180 seconds; S3: Wet mixing: Add pure water to the vacuum paste machine and wet mix for 240 seconds; S4: Acid stirring: Add 1.400g / cm 3 6% to 8% dilute sulfuric acid is stirred for 10 to 20 minutes to obtain lead paste, 1.400g / cm 3 Dilute sulfuric acid is added in several portions; S5: Plate production: Apply lead paste on the mesh belt to form the plate. S6: Curing: Remove the plate and place it on the curing rack, then push the curing rack into the curing room for curing. The curing includes a high humidity stage, an oxidation stage and a drying stage. The high humidity stage lasts for 24 to 30 hours, the oxidation stage lasts for 15 to 20 hours, and the drying stage lasts for 15 hours. S7: Formation: After the cured plates are assembled into semi-finished batteries, they are formed by a process of eight charges and seven discharges.
3. A long-life lead-carbon battery positive electrode production process according to claim 2, characterized in that: In step S2, the lead powder is divided into two portions and added to the vacuum paste machine in two times. The first portion is first added to the vacuum paste machine, and then the additive is added and stirred, and the second portion is added to the vacuum paste machine.
4. A long-life lead-carbon battery positive electrode production process according to claim 3, characterized in that: The time for adding pure water in step S3 is controlled within 80 seconds.
5. A long-life lead-carbon battery positive electrode production process according to claim 4, characterized in that: In step S4, dilute sulfuric acid is added in a total of 6 times, the first acid addition amount is 25% / vacuum degree 535mba / 160 seconds, the second acid addition amount is 30% / vacuum degree 530mba / 156 seconds, the third acid addition amount is 25% / vacuum degree 435mba / 156 seconds, the fourth acid addition amount is 10% / vacuum degree 425mba / 55 seconds, the fifth acid addition amount is 5% / vacuum degree 280mba / 28 seconds, and the sixth acid addition amount is 5% / vacuum degree 180mba / 22 seconds.
6. A long-life lead-carbon battery positive electrode production process according to claim 5, characterized in that: In step S4, the paste temperature is controlled within 45°C.